The Impact of Energy Transition Risks on the Sustainable Development of Kazakhstan’s Economy - B. S. Saubetova; G. A. Saimagambetova; A. I. Esturlieva; G. D. Amaniyazova (Экономика: стратегия и практика)
The purpose of the study is to determine the prospects and difficulties of Kazakhstan’s energy transition, as well as to analyze the direction of development of the electric power sector to overcome the difficulties that have developed today. The global trends of transition to a carbon-free economy, the foundation for which was laid during the crisis of 2008, are currently being strengthened under the influence of two factors. Firstly, the fact of climate change as a result of anthropogenic impact is recognized by the world community. Secondly, the economic crisis caused by the COVID-19 pandemic has pushed many states, investors, as well as private companies to more actively implement decarbonization strategies. This is not only due to concern about increasing environmental problems. Decarbonization and energy transition can become an effective tool for stimulating economic development through the development of technology, attracting investment and creating new jobs. The analysis of the consequences of the considered trend for Kazakhstan is carried out. It is shown that the country’s strategic documents reflect a cautious approach based on plans to increase hydrocarbon exports. However, we believe that maintaining this approach is fraught with a number of economic and political risks. According to the results of the study, the importance of developing comprehensive strategic approaches aimed at leveling the identified risks is emphasized, and specific proposals for the implementation of a gradual energy transition in Kazakhstan are formulated.